2017
DOI: 10.21660/2017.31.6536
|View full text |Cite
|
Sign up to set email alerts
|

3d-Fem Analysis of Shield Tunnel Construction With Ground-Spring Model

Abstract: ABSTRACT:The shield tunneling has been extensively implemented for construction of underground transportation systems in urban areas. Reports on tunnel segment damage during tunnel construction become increasing. The jack thrust force is the essential cause of damage to the segment. The objective of this article is to present the model which analyzes the behavior of tunnel lining during construction. The model consists of five rings and ten segments for each ring connected together with the shear springs which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Moreover, evidence had shown that Stone Age people, Egyptian, Romans and other civilizations had developed different tunneling technologies to obtained metals and gold [1,2]. With modern excavation tools and analysis techniques both soil and rock tunneling has become an inevitable part of smart cities [3,4]. Researchers have studied the response of tunnels due to internal and external loadings [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, evidence had shown that Stone Age people, Egyptian, Romans and other civilizations had developed different tunneling technologies to obtained metals and gold [1,2]. With modern excavation tools and analysis techniques both soil and rock tunneling has become an inevitable part of smart cities [3,4]. Researchers have studied the response of tunnels due to internal and external loadings [5,6].…”
Section: Introductionmentioning
confidence: 99%